Pleasure as a mediator of economic benefit and online impulse buying among Generation Z TikTok Live users in Semarang - Labib Ikhsan Putrantino; Fatimah Bala Haladu (Novera: Journal of Economics and Business, 2026)
Live commerce increasingly encourages impulse buying, yet the effect of economic benefit on online impulse buying remains inconsistent, while the emotional mechanism of pleasure requires further clarification. This study aims to examine the effect of economic benefit on online impulse buying and the mediating role of pleasure among Generation Z users of TikTok Live Streaming in Semarang. Using a quantitative explanatory approach, data were collected from 130 respondents selected through purposive sampling and analyzed using PLS-SEM with SmartPLS 4. The results show that economic benefit has no significant direct effect on online impulse buying (β = 0.186; p = 0.072), but significantly affects pleasure (β = 0.562; p < 0.001), which subsequently influences online impulse buying (β = 0.400; p < 0.001). The indirect effect is also significant (β = 0.225; p < 0.001). These findings demonstrate that pleasure functions as an emotional mechanism through which economic benefit is translated into online impulse buying. Abstrak Perdagangan berbasis siaran langsung semakin mendorong pembelian impulsif, tetapi pengaruh economic benefit terhadap online impulse buying belum konsisten dan mekanisme emosional pleasure masih perlu diperjelas. Penelitian ini bertujuan menganalisis pengaruh economic benefit terhadap online impulse buying serta menguji peran pleasure sebagai mediator pada Generasi Z pengguna TikTok Live Streaming di Semarang. Penelitian menggunakan pendekatan kuantitatif eksplanatori dengan 130 responden yang dipilih secara purposive sampling dan dianalisis menggunakan PLS-SEM melalui SmartPLS 4. Hasil menunjukkan bahwa economic benefit tidak berpengaruh langsung terhadap online impulse buying (β = 0,186; p = 0,072), tetapi berpengaruh positif terhadap pleasure (β = 0,562; p < 0,001), yang selanjutnya berpengaruh terhadap online impulse buying (β = 0,400; p < 0,001). Efek mediasi juga signifikan (β = 0,225; p < 0,001). Temuan ini menegaskan bahwa pleasure berfungsi sebagai mekanisme emosional yang menerjemahkan manfaat ekonomi menjadi pembelian impulsif.